Impact of thinning intensity on the diameter and height growth of Larix kaempferi stands in central Korea. Issue 2 (2nd April 2016) - Kim, Moonil; Lee, Woo-Kyun; Kim, Yoo-Seoung; Lim, Chul-Hee; Song, Cholho; Park, Taejin; Son, Yowhan; Son, Yeong-Mo
Abstract : The objective of this study was to examine the effect of thinning intensity on the diameter at breast height (DBH) and height growth of Japanese larch ( Larix kaempferi ) stands located in the Yangpyeong-gun region of central Korea. In addition, a growth model was developed from the thinning practice. Four sample plots were prepared separately and thinned at different intensities (0%, 10%, 20%, and 40% cutting based on the number of trees, respectively) in 1997. DBH and height of individual trees were measured independently in 1997 and 2009. The mean DBH for LT00, LT01, LT02, and LT03 increased from 12.0, 12.1, 12.0, and 12.7 cm in 1997 to 15.3, 16.1, 16.2, and 17.1 cm in 2009, respectively. In addition, the mean height for each plot increased from 11.9, 13.5, 13.6, and 12.0 m in 1997 to 17.0, 17.0, 17.1, and 18.1 m in 2009, respectively. Thinning intensity was found to have a significant positive effect on DBH growth ( P < 0.05), whereas there was no definite effect on height growth ( P > 0.05). This result can be attributed to the fact that thinning promotes DBH growth by reducing horizontal-spacing competition between neighboring trees for securing sunlight and growing space. The developed growth model with our results showed a high degree of reliability ( R 2 = 0.86) and could generalize the thinning intensity based on DBH growth.